Cajoling or coercing: would electoral engineering resolve the young citizen–state disconnect?. (20th October 2016) - Henn, Matt; Oldfield, Ben
ABSTRACT: The relationships between citizens and their states are undergoing significant stresses across advanced liberal democracies. In Britain, this disconnect is particularly evident amongst young citizens. This article considers whether different electoral engineering methods – designed either to cajole or compel youth to vote – might arrest the decline in their political engagement. Data collected in 2011 from a national survey of 1025 British 18-year-olds and from focus groups involving 86 young people reveal that many young people claim that they would be more likely to vote in future elections if such electoral reforms were implemented. However, it is questionable whether or not such increased electoral participation would mean that they would feel truly connected to the democratic process. In particular, forcing young people to vote through the introduction of compulsory voting may actually serve to reinforce deepening resentments, rather than engage them in a positive manner.